2012
DOI: 10.6061/clinics/2012(02)07
|View full text |Cite
|
Sign up to set email alerts
|

Liver enzymes in patients with chronic kidney disease undergoing peritoneal dialysis and hemodialysis

Abstract: OBJECTIVE:The present study was designed to analyze the serum levels of aspartate and alanine aminotransferases, gamma-glutamyl transferase, and the hematocrit in patients with chronic kidney disease who were undergoing peritoneal dialysis or hemodialysis.PATIENTS AND METHODS:Twenty patients on peritoneal dialysis and 40 on hemodialysis were assessed, and the patients were matched according to the length of time that they had been on dialysis. Blood samples were collected (both before and after the session for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 21 publications
2
25
1
Order By: Relevance
“…So, recognition of liver damage may be hampered by the reduction in aminotransferase values in HD patients. Possible underlying reasons may be related to pyridoxine deficiency or maybe by the presence of an inhibitory substance in the uremic milieu, but the exact mechanism is still unknown [18]. The evaluation of liver fibrosis/steatosis by non-invasive methods such as TE may represent a potential future approach to the non-invasive assessment of liver steatosis/fibrosis in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…So, recognition of liver damage may be hampered by the reduction in aminotransferase values in HD patients. Possible underlying reasons may be related to pyridoxine deficiency or maybe by the presence of an inhibitory substance in the uremic milieu, but the exact mechanism is still unknown [18]. The evaluation of liver fibrosis/steatosis by non-invasive methods such as TE may represent a potential future approach to the non-invasive assessment of liver steatosis/fibrosis in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased ALT resulted from a reduced liver size and liver blood ow and was associated with aging, frailty, and higher mortality in the general elderly population [26,27]. There is a correlation between ALT levels and the severity of renal failure [15].…”
Section: Discussionmentioning
confidence: 99%
“…Patients on dialysis had reduced serum levels of aminotransferases, which suggested that the ALT levels were reduced concomitantly with the progression of renal dysfunction [14,15]. Previous study demonstrated that ALT levels have a negative correlation with the severity of renal failure, resulting in high AST/ALT ratio in PD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was in one study an increase in the sensitivity of ALT from 55% to 76% for the diagnosis of discrete liver diseases and specificity was reduced from 97% to 89% when the ULN was reduced [11,12]. A second study found the risk of mortality from liver disease was higher in individuals with normal levels of ALT that were close to the ULN compared with individuals with lower ALT levels in a large Korean population.…”
Section: Introductionmentioning
confidence: 98%